2016
DOI: 10.1101/cshperspect.a028043
|View full text |Cite
|
Sign up to set email alerts
|

The Epilepsy Spectrum: Targeting Future Research Challenges

Abstract: There have been tremendous recent advances in our understanding of the biological underpinnings of epilepsy and associated comorbidities that justify its representation as a spectrum disorder. Advances in genetics, electrophysiology, and neuroimaging have greatly improved our ability to differentiate, diagnose, and treat individuals with epilepsy. However, we have made little overall progress in preventing epilepsy, and the number of patients who are cured remains small. Likewise, the comorbidities of epilepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…However, it has been suggested that most epilepsies have a polygenic basis, with multiple genetic susceptibility factors which have only partial effects, but act in concert, and interact with various environmental factors (Ferraro and Buono, 2006; Tan and Berkovic, 2010). The genes associated with epilepsy are involved in different molecular pathways, including the regulation of development and function of the nervous system (Holmes and Noebels, 2016). Although, the majority of genes associated with epilepsies are coding for different voltage and ligand-gated ion channels or regulating the action of excitatory or inhibitory neurotransmission (i.e., CHRNA4, CHRNA2, CHRNB2, GABRG2, GABRA1, KCNQ2, KCNQ3, SCN1B, SCN1A, SCN2A), the potential role of several other genes (i.e., ARX, CDKL5, LGI1, PCDH19, SLC2A1, SPTAN1, STXBP1) in the epilepsy has also been also suggested (Rees, 2010; Hildebrand et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that most epilepsies have a polygenic basis, with multiple genetic susceptibility factors which have only partial effects, but act in concert, and interact with various environmental factors (Ferraro and Buono, 2006; Tan and Berkovic, 2010). The genes associated with epilepsy are involved in different molecular pathways, including the regulation of development and function of the nervous system (Holmes and Noebels, 2016). Although, the majority of genes associated with epilepsies are coding for different voltage and ligand-gated ion channels or regulating the action of excitatory or inhibitory neurotransmission (i.e., CHRNA4, CHRNA2, CHRNB2, GABRG2, GABRA1, KCNQ2, KCNQ3, SCN1B, SCN1A, SCN2A), the potential role of several other genes (i.e., ARX, CDKL5, LGI1, PCDH19, SLC2A1, SPTAN1, STXBP1) in the epilepsy has also been also suggested (Rees, 2010; Hildebrand et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in its promoter region are reported to reduce SCN1A transcription, which causes SCN1A haploinsufficiency. Accordingly, the reduced sodium currents in GABAergic inhibitory neurons may cause hypoexcitability of inhibitory neurons, leading to epilepsy 36 . It is unclear how the deletion within the hGPR56 e1m non-coding region led to epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy-associated genes encode for ion channel and synaptic proteins, as well as cell adhesion molecules, signaling proteins and transcription factors. The mechanisms through which mutations in such different genes lead to epileptic seizures are largely unknown, although they ultimately lead to brain hyperexcitability [9].…”
Section: Introductionmentioning
confidence: 99%